2013
DOI: 10.1002/ajpa.22285
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints: Diet and dietary adaptations in early hominins: The hard food perspective

Abstract: Recent biomechanical analyses examining the feeding adaptations of early hominins have yielded results consistent with the hypothesis that hard foods exerted a selection pressure that influenced the evolution of australopith morphology. However, this hypothesis appears inconsistent with recent reconstructions of early hominin diet based on dental microwear and stable isotopes. Thus, it is likely that either the diets of some australopiths included a high proportion of foods these taxa were poorly adapted to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
85
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 117 publications
(328 reference statements)
5
85
0
2
Order By: Relevance
“…Recent challenges to the efficacy of microwear as a tool for reconstructing diet center on the notion that "the geometry of microwear features depends critically on the hardness (i.e., resistance to indentation) of microscopic particles in relation to that of enamel," and that phytoliths are not "hard enough to create steep, sharp angled pits or scratches on enamel surfaces" (22). These arguments are based on the innovative nanowear experiments of Lucas et al (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recent challenges to the efficacy of microwear as a tool for reconstructing diet center on the notion that "the geometry of microwear features depends critically on the hardness (i.e., resistance to indentation) of microscopic particles in relation to that of enamel," and that phytoliths are not "hard enough to create steep, sharp angled pits or scratches on enamel surfaces" (22). These arguments are based on the innovative nanowear experiments of Lucas et al (19).…”
Section: Discussionmentioning
confidence: 99%
“…6 This diet-microwear pattern association has been used to infer feeding behaviours of many fossil species, including early hominins. 7 However, a recent study 8 has called into question the efficacy of microwear as a proxy for diet, suggesting that experimental validation is needed to affirm relationships between pattern and foods eaten. For example, in an in vitro wear simulation study, Lucas and coauthors 9 found that while quartz dust on foods can easily wear tooth enamel, phytoliths within them might not.…”
mentioning
confidence: 99%
“…This finding has led some to suggest that grit in the environment may be more important to wear pattern than factors intrinsic to items eaten. 10 In fact, Strait et al 8 argued that microwear patterns for early hominins may reflect the dustiness of the environment and, 'say little about the nature of the foods themselves' 8(p.348) . The argument follows that the more striated and less pitted microwear seen for Plio-Pleistocene hominins from eastern Africa than those from southern Africa 7 may have more to do with where they lived than what they ate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential significance of fallback foods has been widely embraced by the anthropological community (e.g., Rosenberger, 2013) and is increasingly used to explain dietary variation and interpret masticatory morphology in a variety of extant and extinct primates (e.g., Alba et al, 2010;Chancellor et al, 2012;Daegling et al, 2013;Doran-Sheehy et al, 2009;Etiendem and Tagg, 2013;Grine et al, 2006aGrine et al, , 2006bGrueter et al, 2009;Hanya and Bernard, 2012;Irwin et al, 2014;Laden and Wrangham, 2005;Porter et al, 2009;Strait et al, 2009Strait et al, , 2013Ungar et al, 2008;Vogel et al, 2009;Wright et al, 2009). One feature linked to the fallback food concept is primate molar enamel thickness Lambert et al, 2004).…”
mentioning
confidence: 99%